2013
DOI: 10.1007/s11604-013-0220-x
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel tuberculosis by multidetector CT enteroclysis

Abstract: Multidetector CT enteroclysis is well tolerable and accurate modality for evaluation and diagnostic characterization of small bowel tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Ray D, et al (2013) observed a sensitivity of 93.75% for CT-EC in diagnosing small bowel tuberculosis. 16 Previous studies have demonstrated a sensitivity of more than 85% for CT-EC/CT-EG in detecting Crohn's disease. 17 The sensitivity of UGIE/ileo-colonoscopy for detecting bowel involvement in cases of intestinal tuberculosis and Crohn's disease in our study was 83.72% and 64.28% respectively.…”
Section: Comparison Of Incidence Of Associated Extra-intestinal Findimentioning
confidence: 98%
“…Ray D, et al (2013) observed a sensitivity of 93.75% for CT-EC in diagnosing small bowel tuberculosis. 16 Previous studies have demonstrated a sensitivity of more than 85% for CT-EC/CT-EG in detecting Crohn's disease. 17 The sensitivity of UGIE/ileo-colonoscopy for detecting bowel involvement in cases of intestinal tuberculosis and Crohn's disease in our study was 83.72% and 64.28% respectively.…”
Section: Comparison Of Incidence Of Associated Extra-intestinal Findimentioning
confidence: 98%
“…The sensitivity of CTE to detect the bowel lesions is higher than that of ileocolonoscopy as the former not only demonstrates the extraintestinal findings but also permits complete evaluation of all bowel segments 33–37 . In our study, the sensitivity of diagnosing ITB/CD increased from 90.6 to 97.7% by combining findings on CTE with ileocolonoscopy, suggesting that all mucosal abnormalities cannot be delineated on CTE, and a combination of these two modalities increases the sensitivity of diagnosis.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, the sensitivity of CT enterography for detecting CD and ITB was 78.65% and 75% respectively. Ray D et al [17] observed a sensitivity of 93.75% for CT enterography in diagnosing ITB. The sensitivity of CT enterography has been reported in excess of 85% for diagnosing CD [18][19][20][21].…”
Section: Discussionmentioning
confidence: 98%
“…Ray D et al . [ 17 ] observed a sensitivity of 93.75% for CT enterography in diagnosing ITB. The sensitivity of CT enterography has been reported in excess of 85% for diagnosing CD [ 18 - 21 ].…”
Section: Discussionmentioning
confidence: 99%